Translation Strategies to Deal With Indonesia Censorship Regulation on Movie - Suriadi, M. Agus (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2018)
This study aims to begin an examination into how the censor regulation effect to movie subtitle which were being showed in Indonesia. To reach that, it using qualitative method in particular translations strategy has been existed. It found that various data hardly to deal with the regulation mostly classified into slang expression that effect to the vulgarity and offensive. It happened because the translator hard to find out the equivalence effect by facing the constrain of the time, space, and also scene. The strategies were used to deal with the regulation done by soften strategy the TL by doing paraphrase, modulation, and emphasize related to pragmatic context. The regulation has been ruling in order protect the audiences have been giving them the comfortless to enjoy the movie without worry about reflecting a state of moral or cultural decline to Indonesian people who have multicultural and ethnic. So, the bad word that relating to offensive language must not be found in the outsider movies with Indonesia subtitle.—Penelitian ini bertujuan untuk memulai pemeriksaan terhadap bagaimana efek regulasi sensor terhadap subtitle film yang sedang ditampilkan di Indonesia. Untuk mencapai itu, menggunakan metode kualitatif dalam strategi penerjemahan tertentu telah ada. Ditemukan bahwa berbagai data sulit untuk berurusan dengan peraturan yang sebagian besar diklasifikasikan ke dalam bahasa gaul yang berpengaruh pada vulgar dan ofensif. Itu terjadi karena penerjemah sulit untuk mengetahui efek kesetaraan dengan menghadapi batasan waktu, ruang, dan juga pemandangan. Strategi tersebut digunakan untuk menangani regulasi yang dilakukan dengan melunakkan strategi TL dengan melakukan parafrasa, modulasi, dan menekankan terkait dengan konteks pragmatis. Peraturan tersebut telah berkuasa untuk melindungi penonton yang telah memberi mereka kenyamanan untuk menikmati film tanpa khawatir mencerminkan keadaan penolakan moral atau budaya terhadap orang Indonesia yang memiliki multikultural dan etnis. Jadi, kata-kata buruk yang berhubungan dengan bahasa kasar tidak boleh ditemukan di film-film luar dengan subtitle Indonesia.DOI : 10.15408/bat.v24i1.7132